2006
DOI: 10.1007/s10562-005-9622-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Supported on Mesocellular Silica Foam (MCF) for Oxidative Dehydrogenation of Propane

Abstract: A series of chromium-containing mesocellular silica foam (MCF) catalysts have been prepared and characterized in the oxidative dehydrogenation (ODH) of propane between 350 and 600°C. It is demonstrated that the chromium catalysts supported on MCF exhibit much higher catalytic activity in terms of propane conversion and propylene yield than literature results obtained over chromium-supported mesoporous SBA-15 or MCM-41 catalysts during the ODH of propane. Enhanced catalytic performance of the chromium-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 33 publications
2
29
3
Order By: Relevance
“…The results suggest that there are two kinds of acidic sites and with rise in VO x loading, the catalysts become more acidic. The results are different from those reported by Fan et al [24]. They observed no NH 3 -TPD peaks over SBA-15 whereas over VO x /SBA-15 they detected a wide peak at 205-220°C.…”
Section: Nh 3 -Tpdcontrasting
confidence: 97%
See 1 more Smart Citation
“…The results suggest that there are two kinds of acidic sites and with rise in VO x loading, the catalysts become more acidic. The results are different from those reported by Fan et al [24]. They observed no NH 3 -TPD peaks over SBA-15 whereas over VO x /SBA-15 they detected a wide peak at 205-220°C.…”
Section: Nh 3 -Tpdcontrasting
confidence: 97%
“…The results showed that at vanadium loading of up to 7.2 wt%, the vanadia species are isolated whereas at higher loadings V 2 O 5 crystallites are formed in addition to the monomeric and polymeric vanadia species. Fan and coworkers used VO x /SBA-15 as catalysts for the ODH of propane [24,25]. They found that catalytic activity over VO x /SBA-15 is higher than that of V 2 O 5 /MCM-41 and attributed the enhanced performance to the particularly larger pore size and lower surface acidity of the former.…”
Section: Introductionmentioning
confidence: 99%
“…15 There have been conflicting claims in the literature about the relative catalytic contributions of the different supported VO x structures (isolated VO x species, oligomeric surface VO x species and crystalline V 2 O 5 NPs) to the catalytic activity of supported vanadia catalysts for propane ODH. Some researchers have reported a significant increase in the catalytic turnover frequency (TOF: reaction rate per VO x site) with increasing vanadia loading on the support 8,[16][17][18]20,22,24 while other researchers have found a relatively constant TOF with increasing vanadia loading on the supports. 19,21,23,[25][26][27][28][29][30][31][32] A close examination of the propane ODH catalysis literature reveals several different catalyst synthesis methods have been used by the researchers in this field and it is important to better understand the influence of the different preparation methods on the different supported VO x structures and their specific TOF values.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the extraction performance and stability of the prepared fibers, seven brominated flame retardants (BFRs) were selected as analytes. BFRs have been widely used and caused increasing concern on environmental and human health due to the potential endocrine disruptors [26][27][28]. Tetrabromobisphenol A (TBBPA) was the most used (59%) product because of the ban of polybrominated diphenyl ethers (PBDEs) [29,30].…”
Section: Introductionmentioning
confidence: 99%